2012
DOI: 10.4238/2012.april.10.3
|View full text |Cite
|
Sign up to set email alerts
|

Strategies in identifying individuals in a segregant population of common bean and implications of genotype x environment interaction in the success of selection

Abstract: ABSTRACT. The objective of this study was to compare the BLUP selection method with different selection strategies in F 2:4 and assess the efficiency of this method on the early choice of the best common bean (Phaseolus vulgaris) lines. Fifty-one F 2:4 progenies were produced from a cross between the CVIII8511 x RP-26 lines. A randomized block design was used with 20 replications and one-plant field plots. Character data on plant architecture and grain yield were obtained and then the sum of the standardized v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…In spite of this, the results obtained by the two methods of analysis were similar (Table 4). In other studies, with eucalyptus (Reis et al, 2011) and common bean (Mendes et al, 2012), there were also small unbalanced results similar to those found in this study.…”
Section: Discussionsupporting
confidence: 90%
“…In spite of this, the results obtained by the two methods of analysis were similar (Table 4). In other studies, with eucalyptus (Reis et al, 2011) and common bean (Mendes et al, 2012), there were also small unbalanced results similar to those found in this study.…”
Section: Discussionsupporting
confidence: 90%
“…These differences in families over generations are probably due to generation x family interaction effects. Lima, Ramalho, and Abreu (2012) and Mendes et al (2012), also described the occurrence of this type of interaction.…”
Section: Resultsmentioning
confidence: 90%
“…In addition, considerable emphasis was placed on obtaining information regarding genetic control of quantitative traits. Several studies were performed with the aim of identifying the most promising parental lines and/or segregating populations for selection (Mendes et al 2009, Mendes et al 2012. Studies were also performed to estimate the genetic variance components for several traits by using different estimation methods (Moreto et al 2007, Borel et al 2011).…”
Section: Resultsmentioning
confidence: 99%